Role of Endoplasmic Reticulum Stress in Atherosclerosis and Its Potential as a Therapeutic Target - Yang, Shengjie (Oxid Med Cell Longev, 2020)
Endoplasmic reticulum (ER) stress is closely associated with atherosclerosis and related cardiovascular diseases (CVDs). It occurs due to various pathological factors that interfere with ER homeostasis, resulting in the accumulation of unfolded or misfolded proteins in the ER lumen, thereby causing ER dysfunction. Here, we discuss the role of ER stress in different types of cells in atherosclerotic lesions. This discussion includes the activation of apoptotic and inflammatory pathways induced by prolonged ER stress, especially in advanced lesional macrophages and endothelial cells (ECs), as well as common atherosclerosis-related ER stressors in different lesional cells, which all contribute to the clinical progression of atherosclerosis. In view of the important role of ER stress and the unfolded protein response (UPR) signaling pathways in atherosclerosis and CVDs, targeting these processes to reduce ER stress may be a novel therapeutic strategy.